Esnaflar Arası Komşuluk İlişkileri: Konya Bedesten Çarşısı Üzerine Bir Değerlendirme - Çağlak, Uğur (Muş Alparslan Üniversitesi, 2020)
People in the community interact with each other. Without interaction the individual seemed almost impossible to exist in social life. Interacting in a formal or informal way in the family, kinship, work, school and many other institutions, people also establish a neighbourly relationship. Neighborhood has started to take more place in the social sciences and discussed more, especially in terms of the need for it in urban life and its function in social life. In this study, an evaluation of the neighbourhood, which is one of the important components of the community life, is made of the axis of shopkeepers. In this context, a qualitative study was carried out with the shopkeepers in the Bazaar of Konya, via face to face interview technique. In this research, it is aimed to understand and interpret the perception and sense of neighbourhood, neighbourhood relations as well as the change and transformation of neighbourhood relations in the context of neighbourhood of shopkeepers. As a result of the study, it is seen that neighbourly relations continue between the shopkeepers but recently the neighbourhood relations have decreased and settled on a more shallow ground.

Toplumdaki her insan birbiriyle, çevresiyle etkileşim içindedir. Etkileşim olmadan bireyin sosyal hayatta varlığı neredeyse imkânsız gibidir. Aile, akrabalık, iş yeri, okul ve daha birçok kurumda resmi ya da gayri resmi bir şekilde etkileşim içinde olan insan, komşuluk ilişkisi de kurmaktadır. Komşuluk özellikle kent hayatında kendisine duyulan ihtiyaçtan ve de toplumsal hayattaki işlevi açısından dolayı sosyal bilimler alanında daha fazla yer tutmaya, daha fazla tartışılmaya başlamıştır. Bu çalışmada da toplum hayatının önemli bileşenlerinden biri olan komşuluğun, esnaf komşuluğu ekseninde bir değerlendirmesi yapılmaktadır. Bu bağlamda yüz yüze görüşme tekniği kullanılarak Konya ilindeki bedesten çarşısında bulunan esnaflar ile nitel bir çalışma yapılmıştır. Araştırmada esnaf komşuluğu bağlamında komşuluk algısı ve duygusu, komşuluk ilişkileri ve de komşuluk ilişkilerinin değişim ve dönüşümünü anlamak ve yorumlamak amaçlanmaktadır. Çalışma sonucunda esnaflar arasında komşuluk ilişkilerinin devam ettiği ancak son zamanlarda komşuluk ilişkilerinin azalarak daha yüzeysel bir zemine oturduğu görülmektedir.
Neighborhood Relations Between Tradesmen: An Evaluation on Konya Bedesten Bazaar
anemon
Keywords: Neighbor; Neighborhood; Shopkeepers Neighborhood; Culture; Socialization; komşu; esnaf komşuluğu; sosyal sermaye; Komşuluk; Kültür